Brain metastases from primary tumors. - Hayat, M. A., 1940- (Academic Press is an imprint of Elsevier, 2016)
Brain Metastases from Primary Tumors Volume Three: Epidemiology, Biology, and Therapy of Melanoma and Other Cancers provides a comprehensive overview of the metastasis of cancer, the main cause of approximately 90% of cancer associated deaths, yet the mechanisms governing this clinically important process remain poorly understood. Melanoma is the third most common diagnosis among patients with brain metastases, after lung and breast cancer. Approximately 75% of patients with metastatic melanoma develop brain metastases during the course of their disease. Although tumorigenesis of melanoma remains poorly understood, recent advances in gene expression profiling have revealed molecular mechanisms of this deadly disease. In addition, high-throughput gene expression has many advantages over techniques in cancer transcriptomic studies and has led to the discovery of numerous diagnostic, prognostic, and therapeutic targets, which are also detailed in this book. The book discusses the link between primary tumors and brain metastasis of melanoma, including molecular mechanisms, treatment options, prognosis, and general applications. Comprehensive chapters discuss systemic therapy, integrin inhibitors, stereotaxic radiosurgery, and more, making this book a great resource for neurooncologists, neurosurgeons, neurologists, and cancer researchers.